Blockchain Consensus Mechanisms : A Primer for Supervisors - Bains, Parma (Washington, D.C. : International Monetary Fund, 2022)
Technology plays an increasingly important role in financial services. With the pace of technological inno-vation moving ever faster, the role new technology plays in the provision of financial services is becoming increasingly fundamental. New technology can generate efficiencies for firms, lowering costs that can be passed on to end users. It can increase access to financial services and products for consumers, particularly the most vulnerable; however, new technology can also create new risks and unintended consequences that can harm financial stability, consumer protection, and market integrity. This primer is designed for financial supervisors at central banks, regulatory authorities, and government departments. It adds to existing literature by summarizing key aspects of popular consensus mechanisms at a high level, with a specific focus on how such mechanisms may impact the mandates of supervisors and policymakers when deployed in financial services markets. It could also help inform IMF staff on policy development and technical assistance related to crypto assets, stablecoins, and blockchains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Underground Econom